Tax Control as a Structural Element of Financial Control - Gulmatov Jamoliddin Rakhmatullaevich (Scientific Trends, 2023)
The article is devoted to the consideration of the issues of tax control as a structural element of financial control in the Republic of Uzbekistan. In addition, the article reveals the essence of the forms and types of the tax control.
Keywords: financial control, tax control, tax monitoring, field tax inspection, in-house tax inspection, tax audit.